Kepuasan Muzakki Terhadap Kualitas Pelayanan Zakat Pada BAZ (Badan Amil Zakat) Kabupaten Kerinci - Hendrianto Hendrianto (Institut Agama Islam Negeri (IAIN) Curup, 2016)
The muzakki satisfication towards the service quality in BAZ (Badan Amil Zakat) is different each others. It is because of the complicated-factors. Based on that assumption, the research is focused to measure the muzzaki utility towards the service quality of BAZ, Kerinci District. Applied the quantitative method, the study result a main finding in which the trend of muzakki utility toward BAZ service is good enough. But, in other cases, a part of them feels not enough in satistification. It can be proved from the tangible (CM) score ON 211. Keywords: Muzakki utilty, Service, Quality, Satisfication and Zakat Apparatus.